A rare case report describing the relation between sweet syndrome and spontaneous recurrent peritonitis. (2017) - Rajjoub, Y.; Saffaf, N.; Goodman, A.
Highlights: Sweet syndrome is a rare inflammatory disorder. It can be associated with recurrent spontaneous peritonitis. Abdominal laparoscopy can be a useful diagnostic tool in the assessment and management. Abstract: Introduction: Sweet syndrome (acute febrile neutrophilic dermatosis) is a subset of rare inflammatory disorders, first described by Dr. Robert Douglas Sweet in 1964 (Sweet, 1964). The co-existence of Sweet syndrome and spontaneous recurrent peritonitis has never been previously mentioned in the medical literature. Presentation of case: We report a case of a 37-year old female patient with known idiopathic Sweet syndrome, diagnosed on skin biopsy, who presented with multiple episodes of spontaneous peritonitis. Investigation through abdominal laparoscopy showed large amounts of free pus in the abdomen without bacterial isolation. Discussion: Differential diagnoses, investigations and management of suspected spontaneous peritonitis are discussed. It was suspected that her Sweet syndrome had caused a rare form of previously undescribed recurrent sterile peritonitis. Conclusion: This case illustrates the importance of careful evaluation of patients with known inflammatory disorders, such as Sweet syndrome. It also demonstrates the need to have a multidisciplinary approach, by collaboration between the disciplines of medicine, surgery, microbiology and radiology.